Answers

2014-06-20T13:29:28+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Using fomula of n th term = a + (n - 1)d
given a + (24 - 1)d = 2(a + (9 - 1)d)
solving the equation  we get a = 5d
again taking
a + (24 - 1)d = 2(a + (9 - 1)d)
⇒3a + (72 - 3)d = 6a +54d
⇒(a + (72 - 1)d) + 2 (a - d) = 6a + 54d
⇒(a + (72 - 1)d) = 2a + 10d + 56d
⇒a + (72 - 1)d) = 2(a + (34 - 1)d)
hence proved 72nd term is twice the 34th term.
i am done minor step jumps if you have any problem comment under the answer.
1 5 1